The System of Masoretic Accentuation: Some Introductory Issues - de Hoop, Raymond; Sanders, Paul (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2022)
The goal of this article is to address introductory issues concerning the origin, function, and relevance of the Masoretic accentuation. First, it describes the recent scholarly attitude towards Masoretic accentuation. Then it clarifies some of the terminology involved and shows in which texts the Masoretic accents were used in addition to the Hebrew Bible. Finally, it offers a discussion of the original purpose and function of the Masoretic accentuation.